Alpha-haemoglobin stabilizing protein (AHSP) stabilizes apo-α-haemoglobin in a partially folded state - Krishna Kumar, Kaavya (Biochem J, 2010)
To produce functional haemoglobin, nascent α-globin (α(o)) and β-globin (β(o)) chains must each bind a single haem molecule (to form α(h) and β(h)) and interact together to form heterodimers. The precise sequence of binding events is unknown, and it has been suggested that additional factors might enhance the efficiency of Hb folding. The α-haemoglobin stabilizing protein (AHSP) has previously been shown to bind α(h) and regulate redox activity of the haem iron. Here, we use a combination of classical and dynamic light scattering and NMR spectroscopy to demonstrate that AHSP forms a heterodimeric complex with α(o) that inhibits α(o) aggregation and promotes α(o) folding in the absence of haem. These findings indicate that AHSP may function as an α(o)-specific chaperone, and suggest an important role for α(o) in guiding Hb assembly by stabilizing β(o) and inhibiting off-pathway self-association of β(h).